Ovarian endometroid adenocarcinoma in pregnancy - Živanović Aleksandar; Dimitrijević Aleksandra; Kastratović Tatjana; Đurić Janko; Stanković Vesna; Tanasković Irena (Vojnosanitetski Pregled)
Background. Ovarian cancer is very rare in pregnancy. It is mainly of epithelial origin, low grade and low malignant potential. Case report. We presented a patient in which ultrasound confirmed the presence of clearly limited tumor in the left ovary when she was eight weeks pregnant. The results of 4D Color Doppler showed a central type of tumor vascularisation with resistance index (IR) less than 0.5. The Consultancy Board in Gynecology of the Institute for Oncology and Radiology of Serbia decided to remove the patient's left adnexa and intensively monitor the pregnancy period. The operation (Adnexectomia lateralis sinistra) was performed at 18th week of gestation. Histopathological analysis showed adenocarcinoma invasivum, endometroid well-differentiated type (histological grade I, nuclear grade 2). In 37th week of gestation, the patient gave birth to a male child by cesarean section. In the next 3 years the patient had no subjective interference, laboratory tests and ultrasonographic findings were normal. Conclusion. Ovarian cancer in pregnancy is usually asymptomatic and diagnosed during routine clinical and ultrasound examination. The color Doppler technique have particular importance in the diagnosis of pathological blood supply in tumors and in indication of malignant ovarian mass.